English Speaking as a Second Language for Health Sciences’ Undergraduates: Preferred Activities & Motivators - Jayasinghe, Manori; Liyanage, Lakeesha; Wijesekara, Kanchana; Kotapola, Imendra (JEES (Journal of English Educators Society), 2024)
Fluency in English is vital for non - native speakers in Allied Health Sciences. However, undergraduates in English - medium health programs often struggle with oral communication skills. To address this, faculty administrations have implemented various initiatives, though participation rates remain low. This study aimed to explore students' preferred activities and whether their motivation to improve English speaking skills was driven by intrinsic or extrinsic factors. A cross -sectional survey was conducted among first to final-year students in Pharmacy, Nursing, and Medical Laboratory Science (MLS) programs, who are native Sinhala or Tamil speakers. Data were collected through a validated online questionnaire, pilot tested for reliability. Intrinsic and extrinsic motivators were analyzed using a paired sample t-test. Among 277 respondents (Pharmacy 33.2%, Nursing 45.8%, MLS 20.9%), intrinsic motivation was predominant (p<0.001, 95% CI), with future job prospects, personal development, and confidence being key motivators. Common barriers included fear of mistakes, nervousness, and grammar difficulties. Students favored constructive feedback and supportive classroom environments. Preferred activities included presentations during lectures (60.8%) and participation in speaker clubs, with or without resource persons (55.7%). The study recommends more flexible, interactive opportunities like weekly speaker clubs, certification programs, and integrating both informal and professional topics into the curriculum. These findings offer practical strategies for improving language programs in similar educational contexts. HIGHLIGHTS: The study identifies intrinsic motivation as the primary driver for health sciences undergraduates learning English speaking skills, with future job opportunities, personal development, and confidence being key motivating factors. Common barriers to speaking proficiency include fear of mistakes, nervousness, and grammar difficulties, yet students expressed a strong preference for constructive feedback and supportive classroom environments. Recommendations for faculty include implementing flexible, interactive speaking practice opportunities, such as weekly speaker clubs and presentations while moving away from authoritative, compulsory programs to better align with students' interests.